Penerapan E-Learning Di Era Revolusi Industri 4.0 Untuk Menekan Penyebaran Covid-19 : (The Application of E-Learning in the Era of the Industrial Revolution 4.0 to Suppress the Spread of Covid-19) - Boy Indrayana; Ali Sadikin (Jurnal Ilmu Olahraga dan Kepelatihan Indonesia, 2020)
With covid-19 which has become a world pandemic by attacking 215 countries, educators are looking for alternatives in implementing electronic-based learning or commonly called e-learning. E-learning is one of the advances in the era of the industrial revolution 4.0. the purpose of this study is to provide an overview of the application of elearning in the era of the industrial revolution 4.0 in suppressing the spread of the co-19 pandemic in the Department of Sports Education and FKIP training at Jambi University. The research subjects were students of the Department of Sport Education and Coaching FKIP Jambi University. Data collected on line through interviews through the google meeting application. Data were analyzed using the interactive analysis technique of Miles & Huberman. Research reports that (1) Students feel interested in the application of elearning. (2) the application of e-learning makes it easy for students to attend lectures. (3) Application of e-learning can prevent covid-19 transmission on campus. The application of e-learning has obstacles for students who live in remote areas. The application of e-learning makes students independent and have the courage to express opinions. Abstrak. Dengan adanya covid-19 yang telah menjadi pandemi dunia dengan menyerang 215 negara membuat para pendidik mencari alternatif dalam melaksanakan pembelajaran berbasis elektronik atau biasa disebut e-learning. E-learning adalah salah satu kemajuan di era revolusi industri 4.0. tujuan penelitian ini adalah untuk memberikan gambaran penerapan elearning di era revolusi industri 4.0 dalam menekan penyebaran pandemi covid-19 di Jurusan Pendidikan Olah raga dan kepelatihan FKIP Universitas Jambi. Subyek penelitian adalah mahasiswa Jurusan Pendidikan Olahraga dan Kepelatihan FKIP Universitas Jambi. Data dikumpulkan secara on line melalui wawancara melalui aplikasi google meeting. Data dianalisis menggunakan teknik analisis interaktif Miles & Huberman. Penelitian melaporkan bahwa (1) Mahasiswa merasa tertarik dengan penerapan elearning. (2) penerapan e-learning memudahkan mahasiswa dalam mengikuti perkuliahan. (3) Penerapan e-learning dapat mencegah penularan covid-19 di kampus. Penerapan e-learning memiliki kendala bagi mahasiswa yang tinggal daerah terpencil. Penerapan e-learning membuat mahasiswa menjadi mandiri dan memiliki keberanian dalam mengemukakan pendapat.